PENGARUH SERVANT LEADERSHIP TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PT. PEGADAIAN (PERSERO) AREA PONTIANAK - B31111095, RUDY RAENALA (Jurnal Manajemen Update, 2017)
The role of a leader is very large and vital impact on the success of public organizations are also determined by the nature, methods, and the art of leadership. The progress of an organization is determined by the figure of a leader who was liked and respected by his subordinates. In the leadership of a leader should be able to have and unite different fields of expertise, personality, experience and motivation of its leaders but not with leadership airport (servant leadership), which emphasizes the ability of a leader in providing services, of the ministry can have a positive influence to his subordinates without fear, shy and awkward. This study aims to identify and provide empirical evidence about whether the variable Servant Leadership On Job Satisfaction and Employee Performance In PT. Pegadaian (Persero) Area Pontianak. This study uses Path analysis using SPSS 16. The population used is the employees who work in PT. Pegadaian (Persero) Area Pontianak. The sample used by 50 employees of  PT. Pegadaian (Persero) Area Pontianak. The results of this study indicate that the Servant Leadership partially and positive impact on job satisfaction with t count equal to 2,995 with significance level of 0.004, Servant Leadership partially positive and the Employee Performance with t value amounted to 2,828 with significance level of 0.007 and Job Satisfaction partially negatively affect employee performance with the t value of -2145 with a significance level of 0.037 and is jointly variable Servant Leadership affect the Job Satisfaction and Employee performance PT. Pegadaian (Persero) Area  Pontianak. Keywords : Servant Leadership, Job Satisfaction and Performance of Employees.